An assessment on the aerobic and anaerobic capacities of a tennis player - Zaton, M.; Stepien, A, (Human Movement, 2011)
The purpose of this research was to determine the relationship between a tennis players` technical abilities and their capacity evaluated in both a laboratory and on the tennis court. Basic procedures. Twelve tennis players participated in the study. The anaerobic capacity test (Wingate) and the progressive test were performed on a Monark E 895 cycloergometer. The aerobic and anaerobic capacities were evaluated in the laboratory. The Weber capacity test was performed on a tennis court. Main findings. The research did not reveal any significant correlation between the Wingate`s mechanical parameters and the physiological parameters of the Weber test. A correlation of the maximal oxygen uptake with stroke precision on a tennis court can be observed. The research found that the maximal power output (Pmax) and total work (Wtot) found in the laboratory is related to the stroke precision on a tennis court. Conclusions. The results may suggest that both tests can be applied in the assessment of capacity and the effects of training. From the results of the laboratory and on-court tests, it is possible to specify a player`s semi-specific endurance.